Syrilic Traditional Music Training and Mentoring for Students at Yala Rajabhat University Thailand - A. Rahman Rahim; Arifuddin Arifuddin; Haslinda Haslinda; Manavavee Mamah; Kartini Kartini (Journal of Comprehensive Science, 2026)
This study examines the implementation of Sinrilik traditional music training and mentoring for students at Yala Rajabhat University, Thailand, as an effort to preserve intangible cultural heritage and strengthen cross-cultural relations between Indonesia and Thailand. Sinrilik, a performing art combining oral narratives and traditional musical instruments, serves not only as an aesthetic expression but also as a medium for character education, embedding values such as courage, honesty, and the pursuit of knowledge. This program employed a participatory and educational approach, integrating participatory learning, storytelling pedagogy, demonstrations, and reflective discussions. The results indicate that the training successfully enhanced students’ cultural awareness, technical musical skills, and appreciation of local wisdom. Furthermore, the program fostered a sense of identity and belonging among participants, bridging generational and cultural gaps. The establishment of the “Anak Sinrilik Yala” community reflects the sustainability and long-term impact of the initiative, supported by the involvement of local educators. This study concludes that traditional music training can function as an effective instrument for cultural preservation, character education, and cultural diplomacy. It highlights the importance of integrating local cultural content into educational practices to counter the challenges posed by globalization and modernization